The Knowledge of interns of Kerman Medical Sciences University Regarding Child Maltreatment - Behshid Garrusy; Hossein Safizadeh; Reza Tajaddini (Kerman University of Medical Sciences, 2006)
Background: Child maltreatment is not a new phenomenon and all communities have always been involved with various types of this problem Physicians being in the front line of diagnosis of child maltreatment should have adequate knowledge in this regard Objective: To determine knowledge of interns in Kerman Medical Sciences University about child maltreatment Methods: A total of 86 interns participated in this cross sectional study and data gathering was done by a semi structured questionnaire developed according to valid sources of child maltreatment in the literature The questionnaires reliability and validity were assessed (a=085) Based on the percentage of correct answers the level of knowledge was classified as good (>75%) moderate (5075%) and poor (< 50%) Chi square test was used to determine the relationship between knowledge and considered variables Results: Mean knowledge score was 283 (SD=±48) Half of the interns had good knowledge and the other half had not adequate knowledge Interns knowledge about risk factors of child maltreatment was moderate In regard to the symptoms of child maltreatment observable physical signs such as burning or fractures were being considered as the evidence of child maltreatment while psychological signs or those related to sexual abuse were not taken serious None of the demographic features had significant relation with knowledge level of interns Half of the participants had obtained their knowledge during their medical courses Conclusion: The results of this study indicate that interns do not have adequate knowledge toward child maltreatment and considering the similarity of medical education in our country planning educational programs to improve knowledge of Medical students and other health care providers in regard to child maltreatment seems to be highly required